Pengaruh Penggunaan Modal Kerja Terhadap Profitabilitas Pada PT Metrodata Electronics. Tbk - Dian Kurniasih Wahyusari; Elyanti Rosmanidar; Khairiyani Khairiyani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This research was conducted at PT. Metrodata Electronics, Tbk which is listed on the Indonesia Stock Exchange by collecting the necessary data through the Indonesia Stock Exchange (IDX). The purpose of this study was to find out how much influence Cash Turnover, Accounts Receivable Turnover and Inventory Turnover have on increasing Return On Assets (ROA) produced by companies and find out which of the three variables has the most dominant influence on Return On Assets. The research method used by researchers in this study is survey method with a quantitative approach. The data collection technique was carried out by withdrawing the population from the quarterly financial reports at PT. Metrodata Electronics, Tbk from the period 2016 to 2021. The research data was processed using the help of the Statisrical Product and Services Solution (SPSS) computer program version 24. In analyzing and proving this, the normality test, classic assumption test, autocorrelation test, multicollinearity test were used. , multiple regression test t test (partial) and F test (simultaneous) and test the coefficient of determination. Based on partial calculations, namely using the t test, it is known that for Cash Turnover (X1) t calculate (-2.701) > t table (2.073) this shows that Cash Turnover has a significant influence on increasing profitability or Return On Assets (ROA). For Receivables Turnover (X2) tcalculate (1,935) < ttable (2,073) this shows that receivables turnover has no effect on profitability or Return On Assets. While Inventory Turnover (X3) tcalculate (5,772) > ttable (2,073) this shows that inventory turnover affects the increase in profitability or Return On Asset (ROA). for the results of simultaneous hypothesis testing, namely with the F test, Fcalculate (77,908) > Ftable (3,098) were obtained, which means that simultaneously Cash Turnover, Receivables Turnover, Inventory Turnover together affect the increase in Return On Assets (ROA). While the value of the coefficient of determination () is 0.921. This shows that Cash Collection, Receivables Turnover, and Inventory Turnover have an influence of 92.1% on the increase in Return On Assets at PT. Metrodata Electronics, Tbk.